Frequent Interaction and Fast Feedback Predict Perceived Social Support: Using Crawled and Self‐Reported Data of Facebook Users. Issue 4 (18th May 2016) - Seo, Mihye; Kim, Jinhee; Yang, Hyeseung
Abstract : The present study examines if Facebooking can contribute to psychological well‐being and if so, which aspects of Facebook use could play a significant role. Matching crawled data with self‐reported data from mobile Facebook users, we found that more social interactions with Facebook friends and faster friends' reactions to a user's post contributed toFacebook user's perceived social support and ultimately alleviated loneliness. We also found that the association between frequency as well as speed of Facebook social interactions and psychological well‐being were more significant among those who were sensitive to other's behaviors and feelings than those who were not. The theoretical and practical implications of the findings, particularly regarding mobile communication context, are also discussed.